Acute kidney injury in group A streptococcal bacteraemia: incidence, outcome and predictive value of C-reactive protein - Vilhonen Johanna; Koivuviita Niina; Vahlberg Tero; Vuopio Jaana; Oksi Jarmo (TAYLOR & FRANCIS LTD, 2022)
Background: A ubiquitous human pathogen, Streptococcus pyogenes (Group A Streptococcus, GAS) causes infections from mild pharyngitis to severe septic infections. Acute kidney injury (AKI) is a condition of prompt decline of renal function. The aim of the present study was to report the incidence and outcome of AKI in GAS bacteraemia and to evaluate the diagnostic value of serum C-reactive protein as an indicator of AKI.
Methods: All adult patients with GAS bacteraemia treated at Turku University Hospital from 2007 to 2018 were identified and their patient records were scrutinised.
Results: Of 195 included patients, 38 (19.5%) had AKI stage 1, 20 (10.3%) AKI stage 2 and 26 (13.3%) AKI stage 3 and 111 (56.9%) did not have AKI. The adjusted seven-day mortality was significantly higher in AKI stages 2 and 3 compared to the non-AKI group (15% and 19% vs. 3.6%; p = .046 and .006, respectively). Of the survivors, 95.8% met the criteria of renal recovery at discharge. The higher the AKI stage, the higher was the mean serum CRP level on admission. The optimal cut-off for CRP to identify patients with AKI stage 2 or 3 was ≥244 mg/l (sensitivity 82.6% and specificity 75.8%).
Conclusions: AKI is common in patients with GAS bacteraemia and the severity of AKI correlates with the CRP level on admission. The mortality of patients with GAS bacteraemia and AKI is significantly higher than of patients without AKI. Most survivors, however, show renal recovery.Key MessageAKI is common in group A Streptococcal bacteraemia and increases mortality compared to bacteraemia alone. However, renal recovery is also common. A high CRP level on admission correlates significantly positively with the degree of severity of AKI.